Probiotic supplementation for optimizing athletic performance: current evidence and future perspectives for microbiome-based strategies - Teglas, Timea; Radak, Zsolt (Frontiers in Nutrition, 2025)
The association between microbiota and physical activity is currently a key focus in sports performance research, and the effects of probiotics administration on athletes represent a relatively new area of research. While existing research highlights the promising potential of probiotics, our understanding of how they benefit highly active individuals remains incomplete. Nonetheless, it appears that probiotics have a beneficial effect on mental health, cognitive functions, sleep, gastrointestinal, and upper respiratory symptoms in adult humans. Additionally, the probiotic supplementation and their performance effects of different types of exercise are crucial when building a training program. In most cases, probiotic supplementation is effective in two major types of exercise: probiotics show strain and duration-specific effects both on endurance-based and intermittent-exercise associated sport. The supplementation can reduce inflammatory process activity and stress-related factors, e.g., anxiety, depression, in intermittent exercise-associated sports. In endurance-based sports, probiotics enhanced lipid metabolites, including short-chain and polyunsaturated fatty acids, modulated the maximal oxygen capacity, and reduced gastrointestinal symptoms. Exploring the relationship between probiotics, microbiome, and exercise performance could offer valuable insights for optimizing training techniques and strategies for professional athletes.